Ultrafast and selective labeling of endogenous proteins using affinity-based benzotriazole chemistry. Issue 24 (6th June 2022) - Xin, Xiaoyi; Zhang, Yu; Gaetani, Massimiliano; Lundström, Susanna L.; Zubarev, Roman A.; Zhou, Yuan; Corkery, Dale P.; Wu, Yao-Wen
Abstract : Affinity-based benzotriazole (BTA) probes selectively and covalently label native proteins or endogenous proteins in cells with a fast reaction rate. It is enormously useful for characterizing protein function in biological systems and for drug development. Abstract : Chemical modification of proteins is enormously useful for characterizing protein function in complex biological systems and for drug development. Selective labeling of native or endogenous proteins is challenging owing to the existence of distinct functional groups in proteins and in living systems. Chemistry for rapid and selective labeling of proteins remains in high demand. Here we have developed novel affinity labeling probes using benzotriazole (BTA) chemistry. We showed that affinity-based BTA probes selectively and covalently label a lysine residue in the vicinity of the ligand binding site of a target protein with a reaction half-time of 28 s. The reaction rate constant is comparable to the fastest biorthogonal chemistry. This approach was used to selectively label different cytosolic and membrane proteins in vitro and in live cells. BTA chemistry could be widely useful for labeling of native/endogenous proteins, target identification and development of covalent inhibitors.